2021
DOI: 10.3390/su13031047
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Enriched Municipal Solid Waste Compost Increases Yield, Nutrient Content and Balance in Rice

Abstract: Globally a huge amount of municipal solid waste (MSW) is being produced which is very difficult to dispose. Composting of MSW is one of the options of solid waste recycling, but its use by the farmers is limited because of its low nutrient status. This study has considered some organic amendments to increase nutrient status of MSW compost for its potential use as an organic fertilizer in rice cultivation. We prepared three types of amended compost by mixing 20% mustard oil cake (MOC) and 30% poultry manure (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The solitary application of inorganic fertilizers was found inefficient in increasing the crop yield compared to the combined application of organic and inorganic fertilizers [ 7 , 12 ]. Organic fertilizers have more potential in improving crops yield as they contain a high amount of most of the essential plant nutrients ( Table 6 ) and [ 9 , 14 ]. As the C/N ratio of the organic fertilizer was low, the mineralization was faster compared to other organic materials [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The solitary application of inorganic fertilizers was found inefficient in increasing the crop yield compared to the combined application of organic and inorganic fertilizers [ 7 , 12 ]. Organic fertilizers have more potential in improving crops yield as they contain a high amount of most of the essential plant nutrients ( Table 6 ) and [ 9 , 14 ]. As the C/N ratio of the organic fertilizer was low, the mineralization was faster compared to other organic materials [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The different ratios of N, P, and K contents in rice plants under different treatments except for the control confirmed the presence of these nutrients in an amount that can satisfy the requirements for the normal growth and development of rice unless other factors are limiting. Many reports showed that different organic fertilizers/composts are the source of N, P, and K that can improve soil fertility and increase the uptake of these nutrients in grain crops [ 9 , 19 , 24 ]. The continuous use of organic fertilizer along with inorganic fertilizer increased the nutrient uptake and nutrient use efficiency of major nutrients than did the inorganic fertilizers alone [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice (Oriza sativa L.) is one of the major food grains on which 50% of the world population depends on it (Sultana et al, 2021). According to BBS (2019), the average rice yield is about 3.01 t/ ha which occupies 77% of the cultivable land and contributes 10% of the GDP.…”
Section: Introductionmentioning
confidence: 99%